Cartea de debut a Anei Blandiana - Margareta Dumitrescu (Revista de Istorie și Teorie Literară)
The author assesses and also amends some of the data regarding the appearance and „the second appearance” of Ana Blandiana as well as the details of her publication history and censorship.